ANALISIS KONSEP 3A (ATRAKSI, AMENITAS, AKSEBILITAS) DALAM PERENCANAAN PENGEMBANGAN PARIWISATA BERBASIS MASYARAKAT: (STUDI KASUS: DESA UMATOOS, KABUPATEN MALAKA) - MARIUS YOSEF SERAN; Septian Hutagalung; Roseven Rudiyanto; Laurensius Sandrio; Ida Ayu Rostini (Jurnal Penelitian Terapan Mahasiswa, 2023)
This research aims to analyze the 3A (attraction, amenity, accessibility) concept of tourism planning development in Desa Umatoos, Kecamatan Malaka Barat, Kabupaten Malaka. This research uses a qualitative method and the key informants are the representatives of related stakeholders which from academician, business, community, local government, and mass media. This study uses field observations, in depth interview, focus group discussion, and literature studies. The result of the study showed the existence of main tourist attractions, alternative attractions, other potential nature and cultural tourism products in the village, also numbers of supporting facilities and accessibilities. There are also some weaknesses and potential threats that can become obstacles in the whole process of CBT’s planning development. Therefore, it is recommended that stakeholders need to collaborate in the whole aspects of planning development.